Human rights and the environment : conflicts and norms in a globalizing world - Zarsky, Lyuba (Earthscan, 2002)
The impact of environmental damage on human rights - civil political or welfare and labour rights - is becoming ever-more widely appreciated and has direct bearing on the behaviour of companies and their norms of conduct. In this volume contributors draw on the tools and insights of a range of disciplines including law anthropology economics geography and social science to analyze the issues and show how new standards that protect rights and liberties can be established.